Circular wire-bundle superscatterer. (March 2022) - Kosulnikov, Sergei; Vovchuk, Dmytro; Noskov, Roman E.; Machnev, Andrey; Kozlov, Vitali; Grotov, Konstantin; Ladutenko, Konstantin; Belov, Pavel; Ginzburg, Pavel
Highlights: Efficient control of propagation of electromagnetic energy. Realization of a superscatterer, based on a circular bundle of vertically aligned metal wires. Demonstration of the multipolar multiplexing. Constructive interference of several multipoles gains the directivity. Abstract: Scattering cross-section is one of the main properties, characterizing an object in wireless applications. Resonant phenomena increase the electromagnetic visibility of a scatterer while keeping its footprint small. However, the single-channel limit or Chu-Harrington limit imposes a tight upper bound on a scattering cross-section of subwavelength objects. Being derived for a dipolar response, this limitation can be bypassed if several resonances of a structure are spectrally co-located and contribute constructively to the scattering. Subwavelength structures, obeying this design concept though hardly achievable in practical implementations, are called superscatterers. Here we demonstrate a superscatterer realization, based on a circular bundle of vertically aligned metal wires, optimized to demonstrate 5 multipoles, resonating at nearly the same frequency. As a result, the scattering cross-section becomes 12 times larger than object's geometrical cross-section. Owing to the multipolar multiplexing within the structure, the scattering is 7 times larger than the dipole single-channel limit. Additionally, as a result of the constructive interference of several multipoles, scattering directivity up to 10 dB is observed. Wire-bundle superscatterers may become an attractive architecture for many applications, including compact directive antennas, radar chaff and beacons, long-range RFID tags, and many others.